Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the correct definition for [tex]\(\cot \theta\)[/tex], we start by recalling the basic definitions and properties of trigonometric functions in terms of sine ([tex]\(\sin\)[/tex]) and cosine ([tex]\(\cos\)[/tex]).
[tex]\(\tan \theta\)[/tex] is defined as:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} \][/tex]
Given this, the cotangent function, denoted [tex]\(\cot \theta\)[/tex], is known as the reciprocal of the tangent function. Therefore:
[tex]\[ \cot \theta = \frac{1}{\tan \theta} \][/tex]
Using the definition of [tex]\(\tan \theta\)[/tex]:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} \][/tex]
So,
[tex]\[ \cot \theta = \frac{1}{\frac{\sin \theta}{\cos \theta}} \][/tex]
By taking the reciprocal of the fraction, we get:
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} \][/tex]
Now, we compare this result with the given options:
A. [tex]\(\cot \theta = \tan^{-1} \theta\)[/tex]
B. [tex]\(\cot \theta = \frac{\sin \theta}{\cos \theta}\)[/tex]
C. [tex]\(\cot \theta = \frac{\cos \theta}{\sin \theta}\)[/tex]
D. [tex]\(\cot \theta = \frac{1 \theta}{\cos \theta}\)[/tex]
E. [tex]\(\cot \theta = \frac{1}{\sin \theta}\)[/tex]
From our derivation, the correct definition that matches our result is:
C. [tex]\(\cot \theta = \frac{\cos \theta}{\sin \theta}\)[/tex]
So, the correct choice is option C.
[tex]\(\tan \theta\)[/tex] is defined as:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} \][/tex]
Given this, the cotangent function, denoted [tex]\(\cot \theta\)[/tex], is known as the reciprocal of the tangent function. Therefore:
[tex]\[ \cot \theta = \frac{1}{\tan \theta} \][/tex]
Using the definition of [tex]\(\tan \theta\)[/tex]:
[tex]\[ \tan \theta = \frac{\sin \theta}{\cos \theta} \][/tex]
So,
[tex]\[ \cot \theta = \frac{1}{\frac{\sin \theta}{\cos \theta}} \][/tex]
By taking the reciprocal of the fraction, we get:
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} \][/tex]
Now, we compare this result with the given options:
A. [tex]\(\cot \theta = \tan^{-1} \theta\)[/tex]
B. [tex]\(\cot \theta = \frac{\sin \theta}{\cos \theta}\)[/tex]
C. [tex]\(\cot \theta = \frac{\cos \theta}{\sin \theta}\)[/tex]
D. [tex]\(\cot \theta = \frac{1 \theta}{\cos \theta}\)[/tex]
E. [tex]\(\cot \theta = \frac{1}{\sin \theta}\)[/tex]
From our derivation, the correct definition that matches our result is:
C. [tex]\(\cot \theta = \frac{\cos \theta}{\sin \theta}\)[/tex]
So, the correct choice is option C.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.